A meta‐analysis of sex differences in cyber‐bullying behavior: The moderating role of age. Issue 5 (6th August 2014) - Barlett, Christopher; Coyne, Sarah M.
<x xml:space="preserve">Abstract</x> The current research used meta‐analysis to determine whether (a) sex differences emerged in cyber‐bullying frequency, (b) if age moderated any sex effect, and (c) if any additional moderators (e.g., publication year and status, country and continent of data collection) influenced the sex effect. Theoretically, if cyber‐bullying is considered a form of traditional bullying and aggression, males are likely to cyber‐bully more than females. Conversely, if cyber‐bullying is considered relational/indirect aggression, females will be slightly more likely to cyber‐bully than males. Results from 122 effect size estimates showed that males were slightly more likely to cyber‐bully than females; however, age moderated the overall effect. Specifically, females were more likely to report cyber‐bullying during early to mid‐adolescence than males, while males showed higher levels of cyber‐bullying during later adolescence than females. Publication status and year and continent and country of data collection also moderated the overall effect. Aggr. Behav. 40:474–488, 2014. © 2014 Wiley Periodicals, Inc.